(untitled) (Annals of Medical Research, 2021)
Aim: Gastric cancer is one of most common malignancies in the world. In developed countries including Europe and United States, despite the advanced technology, advanced stages of gastric cancer are still common with a poor survival. In this study, we aimed to describe clinicopathological characteristics and outcomes of gastric cancer in patients who were operated in our clinic.Material and Methods: We respectively evaluated a total of 200 patients who underwent gastrectomy, D2 lymph node dissection due to gastric cancer between November 2006 and December 2015. Data including clinicopathologic features, postoperative complications, overall survival and prognostic factors affecting prognosis were analyzed and statistical analysis was performed. Data including clinicopathologic features, postoperative complications, overal survival and prognostic factors affecting prognosis were analyzed and statistical analysis was performed.Results: Of the patients, 134 (67%) were males and 66 (33%) were females. The mean age was 61.36±11.92 (28-91) years. Tumor localization was frequently low (57%). The most common postoperative complication, regardless of the type of gastrectomy, was the surgical site infection. The major of the patients had Stage 3 disease. The median overall survival was 24.9 (0.07-116.3) months and overall survival was 43.7%.Conclusion: Except for early stage, the chance of curative treatment is low in gastric cancer. Early diagnosis and treatment can yield improved outcomes for this patient population. Therefore, it is important to develop national programs for early diagnosis and to develop experienced endoscopists